The Effect on Cape Town's Retail Environment Produced by the Banting Diet and the Purchasing Patterns of Those Who Follow it. - Batchelor, Michaela (The IIE, 2016)
In 2012, South Africans began to experience a revolution in terms of the way they think about food. Respected sports scientist, Professor Tim Noakes came out championing the low carbohydrate high fat (LCHF) diet, also known as the Banting diet, which saw thousands of South Africans converting to an eating lifestyle which promotes high protein consumption and avoidance of carbohydrates. The main concept and purpose of this particular research study is to investigate the effect on Cape Town’s retail environment produced by the Banting diet and the purchasing patterns of those who follow it. The researcher looks at patterns in which carbohydrate consumption has decreased and protein consumption has increased. The study further aimed to examine what effect the Banting diet has had and continues to have on consumer behavior in the grocery sector and how the food retail industry has reacted to the Banting phenomenon. This study adopts a mixed method research approach. Qualitative and quantitative data will be collected through online questionnaires with individuals currently on the Banting diet and personal interviews with industry professionals from local retailers in Cape Town.
Keywords: Purchasing patterns; Banting diet; Consumer behaviour